Perbandingan Pelajaran Bahasa Arab antara Kurikulum 2013 dengan Kurikulum Merdeka - Fadilla, Putri Amanda; Nasution, Nurul Fadilla; S, Sapri; Rahmadi, Ihsan; Siagian, Nur Nani; Khoirunnisa, Ardina; Harahap, Azmi Oktari; Rais, Syazwina Dinda Damara (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the impact of curriculum changes in Indonesia, specifically from the Curriculum KTSP to the Curriculum Merdeka, on Arabic language learning. A literature review method is employed, focusing on the analysis of official documents, literature, and policies related to the implementation of both curricula, especially in the context of Arabic language learning. The results indicate that curriculum changes reflect an adaptation to the dynamics of education, with the Curriculum Merdeka emphasizing learning outside the classroom and providing schools with the freedom to determine teaching methods. The curriculum development foundation in both phases involves philosophical, sociological, psychopedagogical, and theoretical aspects. The strengths of the 2013 Curriculum lie in creativity, innovation, and character education, while the Merdeka Curriculum offers greater flexibility. Implementation challenges include the readiness of educators and students, the development of learning objectives, and students' adaptation to the freedom to choose their learning paths. Thus, this research concludes that adaptation to the dynamics of education and continuous attention to strengthening teachers' skills and students' readiness are key to the successful implementation of curricula in the future.